853 Severe Obstructive Sleep Apnea after Treatment with Phrenic Nerve Implant for Central Sleep Apnea: A Case for Dual Stimulation?. (3rd May 2021) - Sussman, Sarah; Ananth, Ashwin; Fares, Elie; Huntley, Colin; Boon, Maurits; Fast, Zhanna
Abstract: Introduction: The remedē® system is a transvenous phrenic nerve stimulator used to treat central sleep apnea (CSA). It is a safe and effective implantable device that has demonstrated significant improvements in objective sleep and quality of life. While complex sleep apnea represents development of central sleep apnea during treatment with continuous positive airway pressure (CPAP) for obstructive sleep apnea, and has been well-described in the literature, we present a novel case of predominantly central sleep apnea treated with phrenic nerve stimulation with augmentation of obstructive events thereafter. This patient is, at the time of submission, being evaluated for hypoglossal nerve stimulation. Report of case(s): A 63-year-old male patient with a past medical history of hypertension, atrial fibrillation, asthma, chronic obstructive pulmonary disease, GERD, obesity, and prior pulmonary embolism presented to the sleep medicine clinic with complaints of difficulty initiating and maintaining sleep, snoring, multiple nocturnal awakenings, excessive daytime sleepiness, and physical fatigue. On exam, BMI was 30.4, and airway classification was Mallampati 4. Split night polysomnography revealed severe mixed sleep apnea with an overall apnea hypopnea index (AHI) of 58.6 and a central AHI of 53.8 per hour after successful PAP titration at 7 cm H2O. He underwent phrenic nerve stimulator implantation and activation without complications. Phrenic nerve stimulation titration study four months after activation showed a normal central AHI of 4.6 per hour at a therapeutic voltage of 1.6 to 1.9mA, but significantly worse OSA with obstructive AHI of 53.1. In follow up, he reported intolerance of CPAP due to significant nasal congestion as well as asthma. Presently, he is scheduled for drug induced sleep endoscopy to visualize airway obstruction and is being evaluated for Inspire hypoglossal nerve stimulation and nasal surgery. Conclusion: The treatment of sleep apnea has recently evolved rapidly with the development of implantable devices to treat both central and obstructive sleep apnea. We present a novel case of the first known patient to be considered for dual nerve stimulation for sleep apnea. Further study needs to be done to determine the safety and efficacy of concurrent implantable devices for the simultaneous treatment of OSA and CSA. Support (if any):